Who asked Jesus to leave the territory of Gerasa (Mark 5 - Wolmarans, J. L. P. (1994)
It is argued that the owners of the destroyed pigs in Gerasa asked Jesus to leave their territory. The argument is based upon the hypothesis that a culturally institutionalised code existed, which ruled the action to be taken when property in the care of slaves was damaged or disappeared. The purpose of this action was to determine the culpability of the slaves in charge of the property. It is proposed that the episode in question (Mark 5:14-17) was meant to be read against the context of such a code.
Keywords: Mark 5:14-17; Jesus Christ; Theology; Christianity